Identifikasi Permasalahan Kesulitan Belajar IPA di Sekolah Dasar Negeri Dukuh 1 Kabupaten Tangerang - Zuliani, Rizki; Astuti, Kurnia Tri; Netri, Netri (Lembaga Yasin AlSys, 2023)
This study is the first study in the identification of the problems faced in science subjects. The purpose of this research is to identify the underlying science difficulty in elementary school. The study is a quantitative study using descriptive research methods. These data collecting techniques use interview instruments, observation sheets and learning results (cognitive) tests. The findings of this study provide information leading to the difficulty of learning elementary student science. One of the subjects that has to be mastered at an elementary level is the subject of natural science. The implications of elementary science study should make it possible to cultivate the curiosity of learners scientifically. But the reality is not that all trainees have mastered competence as expected. This lack of natural science concepts is due to the difficulty of learners in responding to learning given by their teachers.